(untitled) (Journal of Namibian Studies : History Politics Culture, 2020)
Having reached the territory of British Bechuanaland after crossing the Omaheke in the wake of the Battle of Hamakari in August 1904, Samuel Maharero, Omuhona wOvaherero, addressed a letter to the Magistrate, dated 28 September 1904. The letter is published here for the first time in its original OtjiHerero version. A literal translation into English differs considerably from the one made on the spot by British officials. While the contemporary translation has been the only historiographical source so far, a literal and accurate translation into English provides quite a different reading and suggests a new reasoning.